Optimization of IT-Based Remedial Test to Improve the Economic Ability of OSN-K Students at SMAN 1 Sumberpucung - Adrian Hartanto Darma Sanputra; Tatas Ridho Nugroho; Eliza Silviana Miftakh; Shynta Nuril Rahmawati Ahyar; Venni Ayunda Pratiwi (Dinasti International Journal of Digital Business Management, 2024)
his article discusses efforts to improve the understanding and competence of SMAN 1 Sumberpucung students who will take part in the National Science Olympiad (OSN) at the district level in the field of economics. SMAN 1 Sumberpucung is a school with "A" accreditation in Malang Regency that has received many awards, especially in the non-academic field. Over the past two years, donations about OSN in the economic sector will help them in participating in the district-level OSN event. Student achievement in the academic field is still minimal, one of which is in the OSN event. For the past five years, the students who were appointed to take part in the district-level OSN (OSN-K) in the economic field have not made it to the next stage. The facilities and infrastructure provided by the school are quite adequate, but they still do not take advantage of the use of technology. Therefore, the implementation of an IT-based Remedial Test website is a solution that can be used to deal with these problems. This service was carried out to implement the website in the learning system of students who will take part in OSN-K in the field of economics. Service activities include observation, discussion, website creation, implementation and handover of the website. The results of this service activity show an increase in students' understanding of various forms.